(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
After reviewing the different archaeological and linguistic theories accounting for the Hispanic Celticity, Hispania´s Celtic is explained as an old stage of the Celtic branch, from which Celtiberian developed on the Peninsula as a central linguistic area (with more than a dozen innovatory isoglosses), while remnants of the pre-Celtiberian phase, pre- served in the periphery (cf. Bartoli´s norma delle aree laterali), are still to be found in part of the Hispano-Celtic corpus. Celtiberian as the lan- guage of the central area may be distinguished from the marginal territories by approximately twenty isoglosses. In this context, a number of new etymological approaches is offered.